2022
DOI: 10.1159/000522426
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Pan-Tropomyosin Receptor Kinase Immunohistochemistry as a Screening Tool for the Detection of Neurotrophic Tropomyosin-Related Kinase Fusions: Real-World Data from a National Multicentric Retrospective Study

Abstract: <b><i>Introduction:</i></b> The neurotrophic tropomyosin-related kinase (<i>NTRK</i>) genes encode the tropomyosin receptor kinases (TRKs). Patients with solid tumors harboring an oncogenic <i>NTRK</i> fusion are eligible for treatment with TRK inhibitors. <i>NTRK</i> fusion is often associated with TRK overexpression. Pan-TRK immunohistochemistry (IHC) is used to screen for <i>NTRK</i> fusions, but immunoreactivity patterns are poorly def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…False positivity has been reported in various other sarcomas, including BCOR sarcoma,20,41 undifferentiated uterine sarcoma,20 Ewing sarcoma,41 leiomyosarcoma,26 synovial sarcoma,26 extraskeletal myxoid chondrosarcoma,26 liposarcoma,26 and myxofibrosarcoma 26. A recent study tested 2669 solid tumors with a low probability (<1%) of NTRK fusions and showed that only 10% of pan-TRK + tumors harbored NTRK fusions 42. Second, the sensitivity of pan-TRK immunohistochemistry has been reported in the range of 75% to 88% and is even lower in detecting NTRK3 fusion 38,40,43.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…False positivity has been reported in various other sarcomas, including BCOR sarcoma,20,41 undifferentiated uterine sarcoma,20 Ewing sarcoma,41 leiomyosarcoma,26 synovial sarcoma,26 extraskeletal myxoid chondrosarcoma,26 liposarcoma,26 and myxofibrosarcoma 26. A recent study tested 2669 solid tumors with a low probability (<1%) of NTRK fusions and showed that only 10% of pan-TRK + tumors harbored NTRK fusions 42. Second, the sensitivity of pan-TRK immunohistochemistry has been reported in the range of 75% to 88% and is even lower in detecting NTRK3 fusion 38,40,43.…”
Section: Discussionmentioning
confidence: 99%
“…26 A recent study tested 2669 solid tumors with a low probability (< 1%) of NTRK fusions and showed that only 10% of pan-TRK + tumors harbored NTRK fusions. 42 Second, the sensitivity of pan-TRK immunohistochemistry has been reported in the range of 75% to 88% and is even lower in detecting NTRK3 fusion. 38,40,43 Such a sensitivity implies that 12% to 25% of tumors with NTRK fusions can be missed when using pan-TRK immunohistochemistry as a stand-alone test.…”
Section: Discussionmentioning
confidence: 99%